Parameter extraction of photovoltaic cell using differential evolution method - Ishaque, K. (IEEE, 2011)
This paper proposes a new parameter extraction method of photovoltaic cell, based on the differential evolution (DE) technique. The proposed method requires very few control parameters and converges rapidly to a solution. Furthermore, it can fit the I-V curve very accurately irrespective of the values of the initial parameters guesses. The performance of DE is evaluated against the well known genetic algorithm (GA) using a synthetic and experimental I-V data set. It is found that the DE method fits the I-V curve better than GA, has a lower fitness function value and faster execution time.